Shear-strength capacity assessment of corroded reinforced concrete beam-column joints - Zhang, Xinchen (2020)
Beam-column joints are regions of high inelastic stress concentration in reinforced concrete (RC) frames. Evidence of the vulnerability of the joints to damage during earthquakes is witnessed in panel zone failures. Corrosion of reinforcement will cause the deterioration of joint behavior under seismic actions, especially for structures in coastal areas. In the study described in this paper, the performance of corroded RC interior as well as exterior beam-column joints subjected to simulated seismic loads were investigated by employing a two-dimensional (2D) nonlinear finite-element (FE) OpenSees model of deterioration of materials as well as the bond-slip effects in joints. The accuracy of the model was verified and calibrated by comparing the FE analysis results against experimental results from the literature. After that, a parametric study was performed to investigate the impacts of some key parameters on the shear strength of corroded joints. A total of 360 specimens were simulated based on the FE model. Finally, these important parameters were integrated into two fitting equations to predict the shear strength of corroded interior and exterior beam-column joints.